Corrosion inhibition of sulphate-reducing bacterial by Ag/Cu bimetallic nanoparticles synthesised from ginger extract. (1st December 2022) - Hu, Yujie; Feng, Qing; Zeng, Hao; Banat, Ibrahim M.; Si, Yinfang; Huang, Peixiu; Li, Xiaonan; Sun, Shanshan; Dong, Hao; She, Yuehui; Zhang, Fan
Abstract: The growth of sulphate-reducing bacteria (SRB) in oilfield produced water and resistance to antibiotics has become an important issue for safe and clean production. Bimetallic nanomaterials with antibacterial effects are a potential candidate to confront microbial resistance. Environmentally friendly methods for the synthesis of bimetallic nanomaterials are an important factor to be considered in production. This study proposed a green method to synthesise Ag/Cu bimetallic nanoparticles (BNPs) as novel corrosion inhibitors and biocides using ginger rhizome extracts.The results showed that 6.25 μg mL −1 BNPs synthesised from ginger extract could disrupt the integrity of SRB cells and reduce adhesion on the surface of carbon steel over 65%. The corrosion rate of BNPs-treated SRB cultures on carbon steel was verified by weight tests, decreasing from 0.453 mm·a −1 to 0.05 mm·a −1 . The changes of carbon steel surface morphology and SRB cell structure after BNPs treatment were observed in order to illustrate the inhibition mechanism of BNPs. The corrosive inhibitors prepared by this method have potential in inhibiting the corrosion behaviour of SRBs and are expected for applications in oilfield production for pipeline corrosion protection. Graphical abstract: Image 1 Highlights: Ginger extract can be used for the synthesis of bimetallic nanoparticles (BNPs). BNPs can reduce the adhesion of SRB on carbon steel surface. SRB cells ruptured by BNPs can slow down the rate of weight loss of carbon steel. This paper provides a promising option for reducing the drug resistance of SRBs.